Reading Romans backwards : a gospel of peace in the midst of empire - McKnight, Scot. (Waco, Texas : : Baylor University Press, 2019)
Proposes an innovative New Perspective reading of Romans emphasizing the ecclesiological situation of the original addressees and Paul's pastoral response.
Includes bibliographical references (pages 183-203) and index.
Keywords: Bible. -- Criticism, interpretation, etc